2015
DOI: 10.5194/bg-12-2163-2015
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of PAHs and the PAH-degrading bacteria in the deep-sea sediments of the high-latitude Arctic Ocean

Abstract: Abstract. Polycyclic aromatic hydrocarbons (PAHs) are common organic pollutants that can be transferred long distances and tend to accumulate in marine sediments. However, less is known regarding the distribution of PAHs and their natural bioattenuation in the open sea, especially the Arctic Ocean. In this report, sediment samples were collected at four sites from the Chukchi Plateau to the Makarov Basin in the summer of 2010. PAH compositions and total concentrations were examined with GC-MS. The concentratio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(44 citation statements)
references
References 68 publications
2
42
0
Order By: Relevance
“…Likewise, culture-independent studies supported that Cycloclasticus spp. likely play a major role in the degradation of petroleum polycyclic aromatic hydrocarbons in coastal (Coulon et al, 2012), deep-sea (Cui et al, 2008; Dong et al, 2015; Gutierrez et al, 2015), and estuarine (McKew et al, 2007; Niepceron et al, 2010) sediments.…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, culture-independent studies supported that Cycloclasticus spp. likely play a major role in the degradation of petroleum polycyclic aromatic hydrocarbons in coastal (Coulon et al, 2012), deep-sea (Cui et al, 2008; Dong et al, 2015; Gutierrez et al, 2015), and estuarine (McKew et al, 2007; Niepceron et al, 2010) sediments.…”
Section: Resultsmentioning
confidence: 99%
“…Although, the concentrations of PAHs and polysaccharides of the samples were not determined in this study due to the difficulty of sampling and the limited amount of samples we obtained, these organics have been reported to be common in the deep ocean (Simoneit and Fetzer, 1996; Dong et al, 2015). More than half of the actinobacterial isolates obtained from this research showed the capacity to degrade organic matter, suggesting that actinobacteria may contribute to the substance and energy flows in biogeochemical cycles in the deep ocean.…”
Section: Discussionmentioning
confidence: 96%
“…PAHs are the main components of petroleum and are introduced into the marine environment by oil spill, river import, natural seepage, hydrothermal activity, and even air current transfer (Latimer and Zheng, 2003). PAHs are persistent organic pollutants that tend to accumulate in marine sediments and have even been reported to be widespread in the deep Arctic Ocean and Pacific Ocean (Simoneit and Fetzer, 1996; Dong et al, 2015). A recent study indicated that hydrocarbon-degrading actinobacteria, notably Dietzia , were abundant in the Arctic deep-sea sediments (0–0.5 mbsf) and were likely to play an important role in PAH degradation in situ (Dong et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Petroleum components have traditionally been divided into four fractions: saturated hydrocarbons, aromatics, resins, and asphaltenes [20]. Normally, saturated hydrocarbons, such as short-chain saturated hydrocarbons and low-molecular-weight aromatics, are the most susceptible to biodegradation, whereas PAHs in aromatics and resins are less vulnerable to microbial attack [21].…”
Section: Introductionmentioning
confidence: 99%